2009
DOI: 10.3329/bjmm.v3i1.2964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Typhidot (IgM) for Early Diagnosis of Typhoid Fever

Abstract: Typhoid fever still continues to be a major public health problem, particularly in many developing countries. A simple, reliable, affordable and rapid diagnostic test has been a long-felt need of the clinicians. We, therefore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Our findings become very significant, because reports from South Asian countries have shown the isolation rate of human-restricted Salmonella spp. ranging between 9.25 and 21% by using only conventional methods (10)(11)(12). Similarly, the specimens collected from chronic typhoid carriers also yielded the bacterium in significantly larger percentages, 42% of cases by acid shock compared to 8.3% by the conventional method (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings become very significant, because reports from South Asian countries have shown the isolation rate of human-restricted Salmonella spp. ranging between 9.25 and 21% by using only conventional methods (10)(11)(12). Similarly, the specimens collected from chronic typhoid carriers also yielded the bacterium in significantly larger percentages, 42% of cases by acid shock compared to 8.3% by the conventional method (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Widal test has been used for over a century in developing countries for diagnosis but it has been reported to have low sensitivity, specificity and positive predictive value [13,14]. We present here an assessment of the utility of Widal test in diagnosing typhoid fever in pediatric patients of New Delhi's one of the largest and the busiest tertiary care hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Almost similar result was found by Indian studies showed a higher positivity by lytic centrifugation method as compared to conventional method [20][21] . Another study from Bangladesh by Begum et al 22 showed that out of 100 clinically diagnosed typhoid fever, 14 were blood culture positive for S. typhi by conventional method. In this study, 6 (4%) of the patients with blood culture-positive by lytic centrifugation method were negative by conventional method.…”
Section: Discussionmentioning
confidence: 99%